2020
DOI: 10.3390/en13040921
|View full text |Cite
|
Sign up to set email alerts
|

A National Strategy Proposal for Improved Cooking Stove Adoption in Honduras: Energy Consumption and Cost-Benefit Analysis

Abstract: The high consumption of firewood in Honduras necessitates the search for alternatives with less-negative effects on health, the economy, and the environment. One of these alternatives has been the promotion of improved cooking stoves, which achieve a large reduction in firewood consumption. This paper presents a cost-benefit analysis for an improved cooking stove adoption strategy for Honduras. The methodology uses the Long-range Energy Alternatives Planning System, LEAP, a tool used globally in the analysis a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…al. [15] found that implementing an improved cookstove strategy is significantly cheaper than non-implementation, while the implementation of an improved efficiency strategy with additional LPG is more expensive than non-implementation.…”
Section: Honduran Primary Solid Biofuel Consumptionmentioning
confidence: 98%
See 3 more Smart Citations
“…al. [15] found that implementing an improved cookstove strategy is significantly cheaper than non-implementation, while the implementation of an improved efficiency strategy with additional LPG is more expensive than non-implementation.…”
Section: Honduran Primary Solid Biofuel Consumptionmentioning
confidence: 98%
“…Other research has examined the costs and benefits of cookstove interventions in Latin America in general and in Honduras specifically. Flores et al [15] recently conducted a cost-benefit analysis of an improved efficiency intervention with and without LPG in Honduras from 2016 to 2030. Our paper complements the work of Flores et al by extending to a wider range of fuel replacements and by considering three key environmental impacts: national level emissions, forest stock depletion, and to a lesser extent, HAP.…”
Section: Research Aim and Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [23][24][25] around the world have been developed using energy planning models such as LEAP in order to evaluate different scenarios for future energy consumption and carbon emissions [26]; to forecast electricity demand [24]; to evaluate the impacts of technological changes [27,28]; energy and urban planning solutions [25]; to develop policies for low carbon development [29,30]. Moreover, the use of energy planning models is essential to identify possibilities through the scenarios built for different sectors, considering the energy supply and demand and a tool to analyze future policies [30].…”
Section: Literature Reviewmentioning
confidence: 99%